2000
DOI: 10.1002/cjce.5450780317
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of pressure fluctuations and minimum fluidization velocity of binary mixtures of geldart group b particles in bubbling fluidized beds

Abstract: A simple method was proposed to find the pressure fluctuations of binary systems of Geldart Group B particles under bubbling fluidized bed conditions. The pressure fluctuations of binary systems could be predicted from the pressure fluctuations of the individual particles component which comprised the binary systems for completely mixed and partially mixed systems. The predicted pressure fluctuations could be used to calculate the minimum fluidization velocity of the binary systems. The predicted and experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…In their turn, particles that tendency to float, in smaller size or lower density, were usually denominated as flotsam. During several years, this terminology has been applied for inert materials, e.g., corundum, glass, iron, polyethylene, polystyrene, steel, ceramic spheres, and sand [3][4][5][6], and currently for biomasses [7][8][9][10].…”
Section: Solid Particle Terminologymentioning
confidence: 99%
See 1 more Smart Citation
“…In their turn, particles that tendency to float, in smaller size or lower density, were usually denominated as flotsam. During several years, this terminology has been applied for inert materials, e.g., corundum, glass, iron, polyethylene, polystyrene, steel, ceramic spheres, and sand [3][4][5][6], and currently for biomasses [7][8][9][10].…”
Section: Solid Particle Terminologymentioning
confidence: 99%
“…Modern procedures such as the evaluation of the pressure fluctuation in the time domain and the power spectrum calculated by the Fast Fourier Transform (FFT) in the frequency domain can also be applied. However, they are frequently used for homogeneous particles [36], since the mechanism of interaction between heterogeneous particles in these procedures is still not well understood [4,37]. The evaluation of these fluctuations allows a better understanding of the fluid dynamics states, consequently leading to the mechanism of mixing and segregation of the particles.…”
Section: Experimental Techniquesmentioning
confidence: 99%
“…Furthermore, an important aspect in binary particle-based fluidized beds is that the minimum fluidization velocity varies non-linearly with bottom or top particles in contrast to a uniformly sized bed, and the particle velocity increases with an increase in the superficial velocity. A comprehensive literature review on the work carried out by the various authors using experimental techniques (Čársky et al, 1987;Hoffmann et al, 1993;Chehbouni et al, 1994;Gauthier et al, 1999;Leu and Wu, 2000;Harris et al, 2002;Ellis et al, 2004;Chew et al, 2010;Mazzei et al, 2010;Rao et al, 2010;Jayarathna and Halvorsen, 2011;Sau and Biswal, 2011;Di Maio et al, 2012;Obuseh et al, 2012;Lan et al, 2014;Philippsen et al, 2015;Leion et al, 2018;Menéndez et al, 2019;Penn et al, 2019;Chew and Cocco, 2021;Emiola-Sadiq et al, 2021;Gupta and De, 2021) and mathematical modeling/CFD (Cooper and Coronella, 2005;Du et al, 2006;Gao et al, 2009;Pei et al, 2010;Zaabout et al, 2010;Chang et al, 2012;Mostafazadeh et al, 2013;Benzarti et al, 2014;Sahoo and Sahoo, 2016;Bakshi et al, 2017;Agrawal et al, 2018;Chang et al, 2019;Daryus et al, 2019;Khezri et al, 2019;Shrestha et al, 2019;…”
Section: Introductionmentioning
confidence: 99%
“…The standard deviation (SD) of pressure fluctuation was also used to determine the minimum fluidization velocity of the binary mixture of solids [31]. Lue and Wu (2000) used the sum of the SD of pressure fluctuation of each species to determine the SD of the binary mixture by multiplying the fraction of each species in the mixture to its corresponding individual SD under the same operating conditions [31]. Pressure fluctuation analysis has also been used to determine the combustion region in a fluidized bed reactor by studying the SD of the pressure fluctuation, and it was found that the combustion region was related to the regions that have high SD values [27].…”
mentioning
confidence: 99%